A Step Towards a Green Future: Does Sustainable Development Policy Reduce Energy Consumption in Resource-Based Cities of China? - Zhang, Haotian; Sun, Xiumei; Ahmad, Mahmood; Lu, Ying; Xue, Chaokai (Frontiers in Environmental Science, 2022)
Undoubtedly, resource-based cities (RBCs) have significantly contributed to the socio-economic development of China; however, energy consumption intensified due to this development. Reducing energy consumption in RBCs and transforming the energy structure of RBCs are major challenges. To promote the energy structure transformation of RBCs, the Chinese government has introduced the Sustainable Development Policy for Resource Cities (SDPRC), but the effectiveness of SDPRC is still unclear. Therefore, this study uses the difference-in-difference (DID) approach to explore the impact of SDPRC on energy consumption scale (ECS) and energy consumption intensity (ECI) in RBCs based on panel data of 280 cities from 2006 to 2019. Firstly, the empirical results indicate that the implementation of SDPRC significantly reduces energy consumption in RBCs. The findings unfold that the inverted U-shaped relationship between SDPRC and ECS, while the effect on ECI has a certain lag, which is significant from the second year, and its impact increases persistently with the advancement of the policy. The stability test also verifies our conclusion. Secondly, the heterogeneity results show that the effect of SDPRC implementation varies across RBCs in different regions and development stages. Thirdly, the impact mechanism test result shows that controlling pollutant emissions and getting rid of resource dependency are important ways to reduce energy consumption in RBCs. However, the implementation of SDPRC does not promote the rationalization and transformation of industrial structure in RBCs. Based on the findings, policy recommendations are proposed for energy transformation and sustainable development of RBCs.